The social life of Indian generic pharmaceuticals in Johannesburg - Kottakkunnummal, Manaf (My University, 2016)
This dissertation attempts to document the social life of Indian generic pharmaceuticals within the broader material culture of pharmaceuticals in Johannesburg. Foregrounding the question of value created in circulation, the study explores how conduits of generic pharmaceutical flow are saturated with the global politics of humanitarianism, locally embedded profitmaking efforts by businesspersons based on risk, cultural moorings of pharmaceutical relations, and historical specificities of locations in which pharmaceuticals have been mobilized for consumption. The central method is the ethnography of circulation. By documenting the ‘moral claims’ of Indian pharma capital as manifested in the public culture of pharmaceutical business, the discussion places the intersectionality of moral and material transactions at the centrestage of pharmaceutical sales and the creation of value
A thesis submitted in fulfilment of the requirement for the degree of Doctor of Philosophy of the Faculty of Humanities of the University of the Witwatersrand, Johannesburg.
Keywords: Pharmaceutical industry--South Africa; Medical anthropology--India; Generic drugs--South Africa; Generic drugs--India